Multilevel optimization of grillages - Belevičius, Rimantas; Valentinavičius, Saulius; Michnevič, Edvard (Journal of Civil Engineering and Management, 2002)
The mathematical models and solution algorithms for optimization of grillage-type foundations are presented. Optimization of grillage is based on optimization of separate beams comprising grillage. Minimising of maximum in absolute value vertical reactive force, bending moment, and reaction-bending moment together is sought in a separate beam. All these problems are non-linear, therefore are solved iteratively changing in each iteration the structure shape to a better neighbouring shape. Solution of this requires three steps: finite element analysis, analytical sensitivity analysis, and optimal re-design via linear mathematical programming. The main problem related to the proposed technique is to guarantee the global minimum solution. Engineering algorithm is suggested for avoidance of local minimum solutions: optimization procedure starts from quasi-optimal initial pile placement scheme, which is designed by a special expert system.Frist Published Online: 30 Jul 2012